2007
DOI: 10.1111/j.1365-2311.2006.00858.x
|View full text |Cite
|
Sign up to set email alerts
|

Host plant finding in the specialised leaf beetle Cassida canaliculata: an analysis of small‐scale movement behaviour

Abstract: Abstract. Host plant finding in walking herbivorous beetles is still poorly understood.Analysis of small-scale movement patterns under semi-natural conditions can be a useful tool to detect behavioural responses towards host plant cues.In this study, the small-scale movement behaviour of the monophagous leaf beetle Cassida canaliculata Laich. (Coleoptera: Chrysomelidae) was studied in a semi-natural arena (r = 1 m). In three different settings, a host (Salvia pratensis L., Lamiales: Lamiaceae), a non-host (Rum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…A recent study by Heisswolf et al (2007) showed that C. canaliculata beetles could find their host plant from a distance of at maximum 50 cm, when a plant individual was offered in a semi-natural arena. However, whether visual or olfactory cues alone or in combination attracted the beetles could not be discriminated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Heisswolf et al (2007) showed that C. canaliculata beetles could find their host plant from a distance of at maximum 50 cm, when a plant individual was offered in a semi-natural arena. However, whether visual or olfactory cues alone or in combination attracted the beetles could not be discriminated.…”
Section: Discussionmentioning
confidence: 99%
“…Within Germany, C. canaliculata is endangered, in Bavaria it is even threatened by extinction (Kippenberg, 2003); however, on warm slopes in the nature reserve 'Hohe Wann' in Northern Bavaria, Germany (50 • 03' N, 10 • 35' E), it is locally abundant (A. Heisswolf and E. Obermaier, personal observations). Only few details are published on the ecology of C. canaliculata (Steinhausen, 1949;Trautner et al, 1989;Heisswolf et al, 2005Heisswolf et al, , 2006Heisswolf et al, , 2007, and little is known about the host recognition pro-Journal of Insect Behavior (2007) 20:247-266 cess in this species. However, as monophagous herbivores the beetles should be very specifically able to recognize their host plant species S. pratensis.…”
Section: Introductionmentioning
confidence: 99%
“…Cain 1985;Crist et al 1992;Turchin 1998;Goodwin and Fahrig 2002;Potting et al 2005;Chapman et al 2007;Heisswolf et al 2007;Roslin et al 2008). Modeling was simplified by the fact that the presence of food plants does not induce a bias in the movement of searching larvae ).…”
Section: Model Construction and Parameterizationmentioning
confidence: 99%
“…Screenshots from the video of each beetle's movements were taken every 3 s and overlain to obtain an image of its walking track, which was converted to top view using Adobe Photoshop 10.0 (San Jose, CA, USA). The straightness of each beetle's movements was then calculated as the ratio between the vector length (from start to end point) to track length, which can range from 0 to 1 (Visser, ; Heisswolf et al., ). Each beetle's track length was measured using Autocad (2007) software (San Rafael, CA, USA), whereas the vector length was a constant 1.5 m (from the center to the edge of the test arena).…”
Section: Methodsmentioning
confidence: 99%